ISOTOPICALLY ANOMALOUS NITROGEN IN H-CHONDRITE METAL - Hashizume K.; Sugiura N. (My University, 1997)
The cause of the nitrogen isotopic anomalies observed by Hashizume and Sugiura (1995) among bulk equilibrated ordinary chondrites has been investigated. The bulk nitrogen isotopic anomalies can be explained by the isotopically anomalous nitrogen dissolved in taenite and/or tetra-taenite (γ/γ' phase Fe-Ni metal). Nitrogen concentrations in taenite range between 5 and 45 ppm, and in most of the samples within 10 +/- 5 ppm. Nitrogen isotopic ratios trapped in taenite vary with samples in a range of -40 < δ15N < +120%%. No systematic correlation was observed between the amounts and the isotopic ratios. Another rather minor nitrogen reservoir seems to exist in nonmagnetic fractions, although the exact host phase has not yet been identified. The isotopic ratios of nitrogen trapped in nonmagnetic minerals generally do not coincide with those in taenite. We consider that the nitrogen dissolved in taenite was trapped there at the end of the thermal metamorphic event when the interior of the H-chondrite parent body was cooled down to 500°C, the closure temperature of nitrogen in γ-Fe,Ni. The concentration and isotopic ratios of nitrogen trapped in taenite reflect the nitrogen equilibrium system within the parent body at =<500°C. The nitrogen isotopic anomalies in taenite cannot be explained by an initially isotopically homogeneous nitrogen reservoir or by processes such as mass-dependent isotopic fractionation.